2011
DOI: 10.1186/1478-811x-9-1
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc modification: why so intimately associated with phosphorylation?

Abstract: Post-translational modification of proteins at serine and threonine side chains by β-N-acetylglucosamine (O-GlcNAc) mediated by the enzyme β-N-acetylglucosamine transferase has been emerging as a fundamental regulatory mechanism encompassing a wide range of proteins involved in cell division, metabolism, transcription and cell signaling. Furthermore, an extensive interplay between O-GlcNAc modification and serine/threonine phosphorylation in a variety of proteins has been reported to exist. However, our unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 17 publications
2
55
0
Order By: Relevance
“…Based on the higher prevalence of Tyr phosphorylation among O-GlcNAc-modified proteins (~68% vs. ~2% in non-O-GlcNAc-modified proteins), Mishra and colleagues suggested that Tyr phosphorylation plays a role in the interplay between O-GlcNAc modification and Ser/Thr phosphorylation in proteins (Mishra et al, 2011). This clearly shows that the interplay between O-GlcNAcylation and phosphorylation is both complex and very extensive.…”
Section: The Interplay Between O-glcnacylation and Protein O-phosphormentioning
confidence: 99%
“…Based on the higher prevalence of Tyr phosphorylation among O-GlcNAc-modified proteins (~68% vs. ~2% in non-O-GlcNAc-modified proteins), Mishra and colleagues suggested that Tyr phosphorylation plays a role in the interplay between O-GlcNAc modification and Ser/Thr phosphorylation in proteins (Mishra et al, 2011). This clearly shows that the interplay between O-GlcNAcylation and phosphorylation is both complex and very extensive.…”
Section: The Interplay Between O-glcnacylation and Protein O-phosphormentioning
confidence: 99%
“…Furthermore, such hypothesis is not tenable to explain the simultaneous downregulation of O-GlcNAc modification in a number of proteins in cancer cells [30]. Although not well understood, such findings are not surprising, keeping in mind that O-GlcNAc modification in protein is a highly regulated process and involved not only O-GlcNAc level, O-GlcNAc cycling enzymes OGT and OGA but also their interacting proteins and various modification status of the substrate itself [9,15]. Delineating the role of O-GlcNAc modification in relation cancer cell metabolism and function would require not only protein specific but also modification site specific approaches, as proteins are often subjected to a number of posttranslational modifications, often with very different and even opposite functional consequences.…”
mentioning
confidence: 93%
“…Together, OGT and OGA dynamically alter the post-translational state and function of proteins in response to cellular signals [9]. O-GlcNAc modification is involved in extensive crosstalk with other posttranslational modifications, such as phosphorylation including tyrosine phosphorylation and virtually all O-GlcNAc modified proteins are phosphoproteins [9,14,15]. As many of the processes that are perturbed in the pathogenesis and progression of cancer involved altered protein phosphorylation, changes in O-GlcNAc modification are likely to have effect on them.…”
mentioning
confidence: 99%
“…Protein glycosylation traditionally refers to the covalent attachment of complex oligosaccharides to proteins in intraluminal compartments or cellular membranes, or in proteins that are destined for secretion. In contrast, O-GlcNAcylation is abundant in cytoplasmic and nuclear proteins, which are modified with a single β-N-acetylglucosamine monosaccharide moiety through an O-β-glycosydic attachment to serine and/or threonine side chains of the polypeptide backbone [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike phosphorylation, which is regulated by hundreds of kinases and phosphatases, O-GlcNAc cycling has only two mediators: the enzymes O-GlcNAc transferase (OGT), and O-GlcNAc amidase (OGA) [2]. The addition and removal of O-GlcNAc is mediated by the concerted action of these two enzymes.…”
Section: Introductionmentioning
confidence: 99%